Extracellular Visfatin Activates Gluconeogenesis in HepG2 Cells Through the Classical PKA/CREB-Dependent Pathway - Choi, Y. J.; Choi, S-E.; Ha, E. S.; Kang, Y.; Han, S. J.; Kim, D. J.; Lee, K. W.; Kim, H. J. (Hormone and Metabolic Research, 2014)
Adipokines reportedly affect hepatic gluconeogenesis, and the adipokine visfatin is known to be related to insulin resistance and type 2 diabetes. However, whether visfatin contributes to hepatic gluconeogenesis remains unclear. Visfatin, also known as nicotinamide phosphoribosyltransferase (NAMPT), modulates sirtuin1 (SIRT1) through the regulation of nicotinamide adenine dinucleotide (NAD). Therefore, we investigated the effect of extracellular visfatin on glucose production in HepG2 cells, and evaluated whether extracellular visfatin affects hepatic gluconeogenesis via an NAD+-SIRT1-dependent pathway. Treatment with visfatin significantly increased glucose production and the mRNA expression and protein levels of phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase) in HepG2 cells in a time- and concentration-dependent manner. Knockdown of SIRT1 had no remarkable effect on the induction of gluconeogenesis by visfatin. Subsequently, we evaluated if extracellular visfatin stimulates the production of gluconeogenic enzymes through the classical protein kinase A (PKA)/cyclic AMP-responsive element (CRE)-binding protein (CREB)-dependent process. The phosphorylation of CREB and PKA increased significantly in HepG2 cells treated with visfatin. Additionally, knockdown of CREB and PKA inhibited visfatin-induced gluconeogenesis in HepG2 cells. In summary, extracellular visfatin modulates glucose production in HepG2 cells through the PKA/CREB pathway, rather than via SIRT1 signaling.
Keywords: visfatin; gluconeogenesis; insulin resistance